(untitled) (Handbook of Treatment Algorithms for Medical and Pharmacy Students, 2025)
Author Miss Veera Naga Lalitha Nakkina, Pharm D Scholar, Koringa College of Pharmacy, Korangi, Tallarevu, Andhra Pradesh, India Abstract Hematologic treatment algorithms are fundamentally dictated by cell lineage, cell maturity, and functional defects. The algorithm for anemias begins with a morphological classification (microcytic, normocytic, macrocytic) based on Mean Corpuscular Volume (MCV). This pathway then uses specific tests (e.g., iron studies, B12/folate levels, reticulocyte count) to differentiate etiologies such as iron deficiency, B12/folate deficiency, or anemia of chronic disease, with treatment aimed at targeted repletion. In contrast, algorithms for leukemias are bifurcated by acuity (acute vs. chronic) and lineage (myeloid vs. lymphoid). Acute leukemias (AML, ALL) are medical emergencies requiring immediate induction chemotherapy. Chronic myeloid leukemia (CML) is managed with a first-line algorithm of oral tyrosine kinase inhibitors. Chronic lymphocytic leukemia (CLL) often follows a "watch and wait" algorithm until symptoms or cytopenias develop. Lymphoma algorithms diverge into Hodgkin (HL) and Non-Hodgkin (NHL) pathways. HL is treated with stage-adapted chemotherapy (e.g., ABVD). NHL algorithms are highly heterogeneous based on subtype, ranging from "watch and wait" for follicular lymphoma to aggressive R-CHOP for diffuse large B-cell lymphoma. Bleeding disorder algorithms differentiate between platelet and factor deficiencies. Immune thrombocytopenia is managed with first-line corticosteroids, while hemophilias require factor replacement algorithms (prophylactic or on-demand). Keywords: Anemia, Leukemia, Lymphoma, Bleeding Disorders, Chemotherapy, Targeted Therapy VIEW PDF